ANALISIS KESALAHAN SISWA SMP KELAS VIII DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) - Rahmawati, Opick; Kadarisma, Gida (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to describe the mistakes made by students and analyze the factors that cause students to make mistakes in solving problems on the SPLDV material. This research was conducted at SMP Pasundan 2 Cimahi grade 8 in the even semester. The subjects of this study were students of grade 8E at SMP Pasundan 2 Cimahi. The data collection technique used in this research is by using the method of written tests and interviews. The methods used in data analysis include data reduction, data presentation and conclusion drawing. The results of data analysis can be concluded that in the process of solving the SPLDV material questions students made several mistakes, namely: 1) conceptual errors; 2) calculation errors, and 3) procedural errors. The factors that make students make these mistakes are the low understanding ability of students in mastering concepts, lack of doing exercises to solve various questions, students tend to be in a hurry when working on questions, lack of accuracy of students in solving problems and the high sense of laziness of students in checking back. the result of the answer.